Experimental comparative study and fracture resistance simulation with irrigation solution of 0.2% chitosan, 2.5% NaOCl and 17% EDTA - Ernani Ernani; Tri Murni Abidin; Indra Indra (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Preparation in endodontic need irrigation materials as root canal debridement and disinfectant. However, irrigation materials is one of the factors that influence the tendency of fracture. Purpose: This study was aimed to see the resistance and fracture distribution if teeth irrigated with high molecular horseshoe crab chitosan at 0.2% concentration, 2.5% NaOCl solution and 17% EDTA solution in endodontic treatment with finite element method (FEM) simulation study and experimental studies. Method: Endodontic treatment performed on 28 maxillary premolars with group A: irrigation solution of 17% EDTA and 2.5% NaOCl solution; group B: 2.5% NaOCl irrigation solution; group C: 2.5% NaOCl irrigation solution and 0.2% chitosan solution; group D: 0.2% chitosan solution irrigation. Final restoration was done using prefabricated glass fiber post. Cementation of post using resin cement then restored with direct composite resin restorations. Pressure test was performed with a Universal Testing Machine with a speed of 0.5 mm/min until fracture occurred. A three dimensional finite element analysis was performed for total deformation, equivalent (von-mises) stress, and equivalent elastic strains. Result: Anova test showed significant differences in fracture resistance (p<0.05) in stroke difference between four groups. Based on the results of the analysis of post-hoc Bonferroni test and LSD, fracture resistance was significantly different between group A (1038.4±201.6) with group C (1515.6±243.3). Kruskal-Wallis test showed no significant difference in the distribution of fractures among the four groups (p>0.05). Statistical analysis showed no significant difference (p>0.05) between the results of experiment and FEM analysis results using the t-test. Conclusion: The results of this study demonstrated that there was effect of the use of high molecular 0.2% chitosan as a combined irrigation with NaOCl, but did not affect the fracture pattern distribution of endodontically treated teeth both experimentally and FEM analysis test.